From Home to Campus: Unveiling Parents' Perspectives on the Resumption of In-Person Classes in Higher Education - Comampong, Normena M.; Tagare Jr., Ruben L.; Calixtro, Marichu A.; Orfrecio, Marlene E.; Esponja, Joanna Caryl P.; Landawe, Bae Kellah Kassandra; Janito, Cheeze R.; Martinez, Norge D. (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the Study: This study explores the challenges faced by parents during the full implementation of in-person classes at the tertiary level and examines their suggestions for improving this transition. Methodology: The study employed a qualitative descriptive research design. In-depth interviews were conducted with ten parents using a guided questionnaire to gather comprehensive insights. Triangulation was used to ensure the reliability and accuracy of the findings. Main Findings: The study highlights the resourcefulness and determination of parents in supporting their children's college education. It uncovers not only tangible successes—such as academic achievements and career prospects—but also narratives of resilience, creativity, and unwavering commitment in overcoming financial, emotional, and unforeseen challenges. Novelty/Originality of this Study: The study presents untold stories of parents' experiences, offering unique perspectives on their struggles and triumphs. These insights can inspire educational practices and policies that better address the needs of families supporting tertiary education in a post-pandemic context.